Locomotor adaptation in people with multiple sclerosis: mechanisms and neuromodulation - Hagen, Andrew Carter, author; Fling, Brett W., advisor; Mañago, Mark M., committee member; Reiser, Raoul F., committee member; Schmid, Arlene A., committee member; Stephens, Jaclyn A., committee member (Colorado State University. Libraries, 2025)
Locomotor adaptation on a split-belt treadmill is a popular motor learning technique where two independent treadmill belts move at different speeds, generating adaptation of stepping over time. Much is understood about the dynamics and neural control of this adaptation, but large questions remain about its long-term retention and applicability beyond controlled laboratory settings. In this dissertation, locomotor adaptability was assessed in people with multiple sclerosis (PwMS), a population with pronounced sensory impairments. This investigation was among the first to show that despite disrupted neural communication, PwMS maintained the ability to adapt their stepping in space and in time in response to the split-belt treadmill. Following, a biomechanical assessment found that for PwMS, increased propulsive force was the largest kinetic contributor to adaptation and was strongly linked to decreased dorsiflexion, indicating that ankle joint dynamics drive much of the observed stepping changes. To address sensory impairments in PwMS, the next study evaluated the use of transcutaneous electrical nerve stimulation (TENS), a neuromodulation method that increases afferent excitability and has been used to improve motor coordination. However, TENS has yet to be investigated in the context of motor learning. This work demonstrated that TENS improved the retention of locomotor adaptation in PwMS after four weeks and decreased cortical activation in both PwMS and healthy controls. These findings suggest that TENS facilitates the recall of motor memories and promotes the automaticity of motor learning, giving it potential as an additional tool to enhance rehabilitation effectiveness in PwMS.
Keywords: locomotor adaptation; multiple sclerosis; transcutaneous electrical nerve stimulation; motor learning; functional near-infrared spectroscopy; step length asymmetry